Dynamic Socio-technical System Design based on Stakeholder Interaction - Albert Fleischmann; Werner Schmidt; Christian Stary (Complex Systems Informatics and Modeling Quarterly)
In order to directly involve stakeholders in socio-technical system design, we argue for streamlining executable process specifications with business process modeling. Due to current agility requirements of organizations, socio-technical system development is considered one of the key activities of members of the organizations. Dynamic process adaptation enable handling the volatility of business operation and IT infrastructure. Subject-oriented process representations are key enablers to dynamic adaptation due to their capability for stakeholders to create directly executable models. In this way stakeholder can be involved in change management pro-actively. Subject-oriented models (i) represent all relevant features required for system control and decision making, and (ii) are executable on demand. This effectiveness enables organizational change in a creative and efficient way, while establishing innovative design and change management tools. Subject-oriented Business Process Management capabilities are reflected in this realm revealing benefits and potential for further research.